Abnormal properties of collagen lysyl hydroxylase from skin fibroblasts of siblings with hydroxylysine-deficient collagen. - Quinn, R S (1976)
Skin fibroblasts from two siblings with hydroxylysine-deficient collagen collagen (Ehlers-Danlos syndrome, type VI) contained normal levels of collagen prolyl hydroxylase activity but were markedly deficient in collagen lysyl hydroxylase activity. The deficiency was evident in all fractions of cell lysates, in low and high ionic strength buffers, and in detergent. Assays of mixtures of wild-type and mutant cell lysates indicated no activation of mutant enzyme by factors in wild-type cells or inhibition of normal enzyme by material in mutant cells. Wild type or mutant cells cultured with ascorbic acid (50 mug/ml of culture medium, added daily) contained approximately the same level of lysyl hydroxylase activity as cells cultured without ascorbate, but prolyl hydroxylase activity without ascorbate was depressed in both an average of 41%. The mutant lysyl hydroxylase was less stable at 37 degrees C than the wild type and did not form high molecular weight aggregates in low ionic strength buffers, as did the control enzyme. The activity of the mutant enzyme was maximally stimulated after dialysis against buffer solutions containing 10 mM dithiothreitol. When assayed in 100 muM dithiothreitol, the mutant enzyme exhibited a higher apparent Km for ascorbate (20 muM) than the wild type (4 muM). In 1.0 mM dithiothreitol the mutant enzyme's apparent Km for ascorbate was reduced to 5 muM. Wild type and mutant enzymes had the same apparent Km for alpha-keto-glutarate (20 muM). The properties of prolyl hydroxylase in wild type and mutant cells were identical: apparent Km's for ascorbate and alpha-ketoglutarate were 100 muM and 20 muM, respectively. If mutant enzyme protein with altered kinetic properties is the only enzyme functioning to hydroxylate lysyl residues in collagen, the variations in hydroxylysine content observed in collagen from different tissues in the subjects reported here could be in part due to differences in cofactor concentrations and in rate and sequence of events in collagen synthesis in different tissues.